Effects of an antioxidant on the shear bond strengths of orthodontic brackets after conventional and laser-assisted extra-coronal bleaching = Efecto de un antioxidante sobre la fuerza de unión de brackets de ortodoncia posterior al blanqueamiento convencional y asistido por láser - Fundaoĝlu Küçükekenci, Funda
Purpose: The purpose of this study was to evaluate the effects of the application of antioxidant on the shear bond strengths (SBS) of orthodontic brackets bonded to human enamel after extra-coronal bleaching with hydrogen peroxide (HP). Materials and methods: Fifty freshly extracted premolars were randomly divided into three groups. One group (Group 1) was bleached with 40% HP (n=20), another group (Group 2) was bleached with 40% HP and activated with an Nd: YAG laser (n=20), and a control group (Group 3) received no treatment (n=10). After the bleaching procedure, Groups 1 and 2 were further divided into two subgroups (Group 1a, Group 1b, Group 2a, and Group 2b). Specimens in Groups 1a and 2a (n=10) received no antioxidant application. A 10% sodium ascorbate solution was applied to specimens in Groups 1b and 2b (n=10). The brackets were then bonded with light-cure adhesive paste to the enamel surfaces of all experimental groups. Specimens were subjected to SBS tests for debonding. Results: The SBS of brackets bonded in Groups 1 and 2 were significantly lower than those of brackets bonded to the control group (p<0.001); however, no statistically significant differences in SBS were noted in Groups 1 and 2 (p>0.001). The antioxidant-treated SBS of brackets in Groups 1b and 2b were significantly higher than those of Groups 1a and 2a (p<0.001). Conclusions: The application of 40% HP had a negative effect on the bond strength. The use of antioxidant for 15 min resulted in the reversal of failed bond strength.